Humans, animals and the craft of slaughter in archaeo-historic societies - Seetah, Krish (Cambridge University Press, 2018)
In this book, Krish Seetah uses butchery as a point of departure for exploring the changing historical relationships between animal utility, symbolism, and meat consumption. Seetah brings together several bodies of literature - on meat, cut marks, craftspeople, and the role of craft in production - that have heretofore been considered in isolation from one another. Focusing on the activity inherent in butcher, he describes the history of knowledge that typifies the craft. He also provides anthropological and archaeological case studies which showcase examples of butchery practices in varied contexts that are seldom identified with zooarchaeological research. Situating the relationship between practice, practitioner, material and commodity, this imaginative study offers new insights into food production, consumption, and the craft of cuisine